An investigation on solar drying: A review with economic and environmental assessment. (15th August 2018) - El Hage, Hicham; Herez, Amal; Ramadan, Mohamad; Bazzi, Hassan; Khaled, Mahmoud
Abstract: In this paper, a review on solar drying is presented. The review comprises the main components, classifications and affecting parameters. Advantages, disadvantages and limitations of such technology are also investigated. That said, solar dryers are assessed according to three key-elements: way of air movement (passive and active), mode of transferring heat (direct and indirect, hybrid and mixed) and type of drying chamber (cabinet, greenhouse and tent). Moreover, economic and environmental studies are performed for the Lebanese case in order to assess the Payback Period (PP) and the amount of CO2 reduction. The examined parameters are the percentage of time where solar dryer is utilized (Pr), the mass of dried food and food type. Results show that for Pr equals to 0.6, when drying 120 kg of carrots using solar dryer the amount of Saved Money (SM) is 780 $/month, PP is 10 months and the amount of CO2 emissions decreases by 6400 kg/month. Highlights: A review on solar drying techniques is presented emphasizing on types, parameters and limitations. Environmental and economic studies are carried out in order to assess solar drying with respect to conventional drying. Depending on the used technique, solar drying allows to decrease CO2 emissions up to 6400 kg/month.